2003
DOI: 10.1029/2001jb000670
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters of acoustic emission events and scaling with mining‐induced seismicity

Abstract: [1] A series of uniaxial compression tests were performed on 96-mm-diameter quartzite samples, 242 mm in length, to understand the scaling of rock fracture processes. Nine acoustic emission (AE) sensors glued to each sample monitored the AEs resulting from microcracking within the samples. In contrast to previous AE studies, the sensors were calibrated as velocity transducers so that the output could be compared to mining-induced seismicity and natural earthquakes. A new hybrid, relative moment tensor method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 50 publications
10
54
0
Order By: Relevance
“…This is consistent with previous work which showed that the largest AEs had predominantly deviatoric focal mechanisms [Sellers et al, 2003;Thompson et al, 2005Thompson et al, , 2009.…”
Section: Focal Mechanismssupporting
confidence: 82%
“…This is consistent with previous work which showed that the largest AEs had predominantly deviatoric focal mechanisms [Sellers et al, 2003;Thompson et al, 2005Thompson et al, , 2009.…”
Section: Focal Mechanismssupporting
confidence: 82%
“…The estimated magnitudes of stress drop were in the same range as those of the AE events associated with fracture of intact rocks (Sellers et al, 2003) and natural earthquakes. The average σ of the small-and the large-sliding events was 6.2±3.2 and 3.1±1.9 MPa, respectively.…”
Section: Source Characteristics Of Aesupporting
confidence: 58%
“…Acoustic emission (AE) events have been observed during frictional sliding on pre-cut faults in laboratory rock samples (e.g., Weeks et al, 1978;Sammonds and Ohnaka, 1998;Yabe et al, 2003). The AE sources were located on the pre-cut fault, and their focal mechanism solution was consistent with that expected theoretically for macroscopic sliding.…”
Section: Introductionmentioning
confidence: 99%
“…If we assume a unity b-value for the GutenbergRichter's relationship, which was also confirmed down to M 0 by the ISS catalog, the fact that our network detected ∼3000 times more events means that we probably detected many events as small as M −3.5 to approximately −4.5. If a 3-MPa stress drop is assumed (Sellers et al, 2003), the source dimension of an M ∼ −4 earthquake is about 0.1 m, which comes into the range of typical laboratory samples. Such a dimension is also consistent with the shortest range of pulse width observed for many events.…”
Section: Discussionmentioning
confidence: 99%